A revision of the Nearctic species of Brachygluta Thomson, 1859 (Coleoptera: Staphylinidae: Pselaphinae) - Chandler, Donald S.; Sabella, Giorgio; Bückle, Christoph (Zootaxa, 2015)
The North American species of Brachygluta Thomson, 1859 are revised, treating a total of 29 species. Six names are placed as junior synonyms: Bryaxis perpunctata Brendel, 1890 (=B. luniger LeConte, 1849), B. labyrinthea Casey, 1894 (=B. intermedia Brendel, 1866), B. loripes Casey, 1894 and B. jacobina Casey, 1908 (=B. foveata LeConte, 1851), B. arizonae Casey, 1887 (=B. texana Casey, 1886), and B. intricata Casey, 1894 (=B. terebrata Casey, 1894). Twelve new Brachygluta species are described: B. chisos Sabella (USA), B. cochimi Bückle (Mexico), B. eldredgei Chandler (USA), B. kiowa Sabella (USA), B. klamath Bückle (USA), B. lareaui Chandler (USA), B. mayo Sabella (Mexico), B. miccosukee Bückle (USA), B. seri Chandler (Mexico), B. shawnee Chandler (USA), B. tamaulipec Sabella (Mexico and USA), and B. wickhami Bückle (USA). Problems with the identities of the following three species based on missing types are discussed: Bryaxis abdominalis Aubé, 1833; Bryaxis curvicera Motschulsky, 1854; and Pselaphus dentatus Say, 1824, with a Neotype being designated for P. dentatus. Nisa Casey, 1886 is removed from synonymy of Brachygluta and reinstituted as a subgenus. A key to the males is provided, nine species-groups are formed and defined, all species are characterized, distributions are detailed, and habitat/collecting data are summarized. Lectotypes are designated for Bryaxis arguta Casey, Bryaxis belfragei LeConte, Bryaxis foveata LeConte, Bryaxis infinita Casey, Brachygluta jacobina Casey, and Brachygluta mormon Bowman.